Insights from epidemiological game theory into gender-specific vaccination against rubella - Eunha Shim; Beth Kochin; Alison Galvani (Mathematical Biosciences and Engineering)
Rubella is a highly contagious childhood disease that causesrelatively mild symptoms. However, rubella can result in severecongenital defects, known as congenital rubella syndrome (CRS), iftransmitted from a mother to a fetus. Consequently, women havehigher incentive to vaccinate against rubella than men do. Withinthe population vaccination reduces transmission but also increasesthe average age of infection and possibly the risk of CRS amongunvaccinated females. To evaluate how the balance among thesefactors results in optimal coverage of vaccination, we developed agame theoretic age-structured epidemiological model of rubellatransmission and vaccination. We found that high levels ofvaccination for both genders are most effective in maximizingaverage utility across the population by decreasing the risk of CRSand reducing transmission of rubella. By contrast, the demands forvaccines driven by self-interest among males and females are $0%$and $100%$ acceptance, respectively, if the cost of vaccination isrelatively low. Our results suggest that the rubella vaccination bymales that is likely to be achieved on voluntary basis withoutadditional incentives would have been far lower than the populationoptimum, if rubella vaccine were offered separately instead ofcombined with measles and mumps vaccination as the MMR vaccine.